2018
DOI: 10.5194/tc-2018-95
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stopping the Flood: Could We Use Targeted Geoengineering to Mitigate Sea Level Rise?

Abstract: Abstract. The Marine Ice Sheet Instability (MISI) is a dynamic feedback that can cause an ice sheet to enter a runaway collapse.Thwaites Glacier, West Antarctica, is the largest individual source of future sea level rise and may have already entered the MISI. Here, we use a suite of coupled ice-ocean flowband simulations to explore whether targeted geoengineering using an artificial sill or artificial ice rises could counter a collapse. Successful interventions occur when the floating ice shelf regrounds on th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Due to the accelerating rise in sea levels, coastal ecosystems (such as marshes and mangroves) could be lost, exacerbating climate damages. Thus, humanity's primary goal in deploying SRM may not be stabilizing temperatures but holding back the sea (Irvine et al, 2012;Zhao et al, 2017;Wolovick & Moore, 2018;Li et al, 2020;Lockley et al, 2020).…”
Section: B) Curbing or Reversing Sea-level Rise [Global Long Term]mentioning
confidence: 99%
“…Due to the accelerating rise in sea levels, coastal ecosystems (such as marshes and mangroves) could be lost, exacerbating climate damages. Thus, humanity's primary goal in deploying SRM may not be stabilizing temperatures but holding back the sea (Irvine et al, 2012;Zhao et al, 2017;Wolovick & Moore, 2018;Li et al, 2020;Lockley et al, 2020).…”
Section: B) Curbing or Reversing Sea-level Rise [Global Long Term]mentioning
confidence: 99%
“…In fact, observations suggest that recent increases in the temperature of water around Antarctica may have already triggered a process that will lead to the collapse of the Pine Island and Thwaites glaciers (Favier et al, 2014;Joughin et al, 2014). Unless an ice stream has exceptionally strong lateral buttressing (Robel et al, 2016), a marine ice sheet instability, once started, may only be stopped by modifying bathymetry to provide extra buttressing, as simulated by flow-band modeling on Thwaites Glacier (Wolovick and Moore, 2018). However, initial results from the BISICLES model evaluating the response of an idealized vulnerable marine glacier to imposed warming found that returning the entire water column to cooler conditions reversed the retreat that had begun during the warming (Asay-Davis et al, 2016).…”
Section: Ice Shelf Collapse and Dynamic Mass Lossmentioning
confidence: 99%
“…In fact, observations suggest that recent increases in the temperature of water around Antarctica may have already triggered a process that will lead to the collapse of the Pine Island and Thwaites glaciers (Favier et al, 2014;Joughin et al, 2014). Unless an ice stream has exceptionally strong lateral buttressing (Robel et al, 2016), a marine ice sheet instability, once started, may only be stopped by modifying bathymetry to provide extra buttressing, as simulated by flow-band modeling on Thwaites Glacier (Wolovick and Moore, 2018). However, initial results from the BISICLES model evaluating the response of an idealized vulnerable marine glacier to imposed warming found that returning the entire water column to cooler conditions reversed the retreat that had begun during the warming (Asay-Davis et al, 2016).…”
Section: Ice Shelf Collapse and Dynamic Mass Lossmentioning
confidence: 99%